The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.11113/jt.v66.1748
|View full text |Cite
|
Sign up to set email alerts
|

Pembinaan dan Penentusahan Instrumen Kemahiran Proses Sains Untuk Sekolah Menengah

Abstract: This study aims to develop a valid and reliable multiple-choice test referred to as Test of Basic and Integrated Process Skills (T-BIPS) for secondary schools to measure the acquisition of a full range of 12 science process skills (SPS), namely 7 basic SPS and 5 integrated SPS. This study involves two phases. Phase one entails the generation of test items according to a set of item objectives, and the establishment of the content and face validities as well as response objectivity in a qualitative manner throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Both groups in this sample demonstrated the same level of achievement, namely moderate achievement in terms of their science process skills level. Ong and Al-Junaidi (2013) found that there was a significant difference between the basic and integrated science process skills with regard to male and female students which was statistically insignificant with the overall score of SPS (p = 0.14> 0.05). This finding was parallel with Ong and Shamalah (2014) who stated that there was no gender difference in terms of students' acquisition in their science process skills.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Both groups in this sample demonstrated the same level of achievement, namely moderate achievement in terms of their science process skills level. Ong and Al-Junaidi (2013) found that there was a significant difference between the basic and integrated science process skills with regard to male and female students which was statistically insignificant with the overall score of SPS (p = 0.14> 0.05). This finding was parallel with Ong and Shamalah (2014) who stated that there was no gender difference in terms of students' acquisition in their science process skills.…”
Section: Discussionmentioning
confidence: 82%
“…The questionnaire is chosen for data collection in order to investigate the Form 2 students' science process skills acquisition level for one district in Sabah state. The Science Process Skills Evaluation Test (SPST) used in the study, as proposed by Ong and Junaidi (2013), was used to measure the students' science process skills acquisition levels. The questionnaire comprised of 35 items which cover both Basic Science Process Skills (BSPS) and Integrated Science Process Skills (ISPS).…”
Section: Instrumentsmentioning
confidence: 99%